PENGELOLAAN SISTEM MASYARAKAT NELAYAN DALAM RANGKA PEMBANGUNAN PERIKANAN DI INDONESIA - Mayudin, Arif; Susanti, Romi (Bioedukasi Jurnal Pendidikan Biologi, 2012)
The potency of fishery and ocean spreading in Indonesia is largely taken benefit especially for fishermen sciety. The fishermen training is very absolute thing for research due to concerning with the training and non formal education. The method applied in the training of the fishermen society is hopefully suitable with the training target, the kind of the method, and those who implement the method. The final result of the implementation of the fishermen society training is producing an intercorrelated end beneficial system in order to increase the walfare or the fishermen.Â Kata kunci: Â Masyarakat Nelayan, Pembinaan Masyarakat, Pembangunan Perikanan